(untitled) (مجلة المنصور, 2022)
In this paper linear array antenna is presented, with elements of rectangular micro strip antenna with corner feeding offering dual-band operation (890-960) MHz GSM and (1.71-1.88) GHz DCS bands. This design is suitable for mobile communication system (base-station). In this paper, a simple technique is used for obtaining dual frequency operation for a rectangular microstrip antenna such that the length of the element resonant at one frequency and the width at another frequency. This paper is divided into three parts, the first part is related with the design of rectangular microstrip antenna with corner feeding and its performance (impedance, directivity, radiation pattern), the second part is related with design of linear array with its feed network and transformers, while the third part is related to the calculation of the base station antenna coverage.